The Ambivalence Of Museum Discourses About “The Other" In Slovenia During The Non-Aligned Movement: Building National Identity And Claiming Belonging To The Civilized West - Palaić, Tina (Lidé města, 2024)
The author focuses on the exhibition narratives that were produced at the Museum of Non-European Cultures which operated between 1964 and 2001 as a dislocated unit of the Slovene Ethnographic Museum. Situated in the baroque Goričane mansion near Ljubljana, Slovenia, it was the first institution in Yugoslavia dedicated to collecting and presenting non-European ethnological heritage. Through its own and visiting exhibitions the Goričane Museum shaped various narratives about the other. Some served to build affinity with other continents and their people, others to move away from them, closer to the developed West. The author examines the exhibition narratives that helped shape national identity and support the idea of belonging to the civilized West.